Psychology of programming: Looking into programmers’ heads - Sajaniemi, Jorma (Human Technology, 2008)
Psychology of programming (PoP) is an interdisciplinary area that covers research into computer programmers’ cognition; tools and methods for programming related activities; and programming education. The origins of PoP date back to late 1970s and early 1980s, when researchers realized that programming tools and technologies should not be evaluated based on their computational power only, but also on their usability from the human point of view, that is, based on their cognitive effects. The hope of such a new approach was that programmers would make fewer errors, produce better software, and work more efficiently. In the first Workshop on Empirical Studies of Programmers, Ben Shneiderman listed “several important destinations for researchers: refining the use of current languages, improving present and future languages, developing special purpose languages, and improving tools and methods” (Shneiderman, 1986, p. 1). During the past two decades, the flow of new languages, tools, and methods has increased rapidly, the scope of programming work has expanded, and research interests have extended to cover group activities. Yet the main goal of PoP—to assist programmers through the benefits of cognitive research—has remained.